Towards Smart Bureaucracy: Digitalization and Resilience of Local Governance in Makassar City - Uddin B. Sore; Muh.Syukri; Andi Akbar; Muhammad Isnan Rasyidi (CV. Creative Tugu Pena, 2026)
This research departs from the problem of not optimal implementation of bureaucratic digitalization in Makassar City. This study aims to analyze the dynamics of bureaucratic digitalization and the obstacles faced in building resilience of local governance in Makassar City. The method used is a qualitative approach through interviews, observations, and documentation studies that are analyzed with the help of NVivo 12 Plus software. This study shows that bureaucratic digitalization in Makassar City is not just a technological process, but a structural and cultural transformation that determines the resilience of local governance. Its success depends heavily on the ability to overcome obstacles such as low digital literacy of apparatus, weak coordination between OPDs, resistance to change, and limited digital infrastructure. Effective digitalization must be understood as a strategy to build an adaptive and innovative bureaucracy through strengthening SPBE, cross-sector collaboration, and community-oriented public service ethics. Thus, digital transformation plays an important role in creating a smart, resilient, competitive, and sustainable bureaucracy in the face of the dynamics of modern governance. Thus, the success of bureaucratic digitalization in Makassar City depends on the ability of local governments to build synergy between technology, human resources, and public service values to realize smart and sustainable governance. This study concludes that digitalization in Makassar City is a fundamental structural and cultural transformation that determines the resilience of local governance. An NVivo 12 Plus-based analysis identified four main obstacles to realizing a smart bureaucracy: low digital literacy among civil servants (35%), sectoral ego barriers (25%), work culture resistance (20%), and limited infrastructure (20%). As a theoretical contribution to local organizational resilience, this study recommends halting the